Targeting hypoxia-induced tumor stemness by activating pathogen-induced stem cell niche defense - Bhuyan, Seema; Pal, Bidisha; Pathak, Lekhika; Saikia, Partha Jyoti; Mitra, Shirsajit; Gayan, Sukanya; Mokhtari, Reza Bayat; Li, Hong; Ramana, Chilakamarti V.; Baishya, Debabrat; Das, Bikul (Frontiers in Immunology, 2022)
Tumor hypoxia and oxidative stress reprograms cancer stem cells (CSCs) to a highly aggressive and inflammatory phenotypic state of tumor stemness. Previously, we characterized tumor stemness phenotype in the ATP Binding Cassette Subfamily G Member 2 (ABCG2)–positive migratory side population (SPm) fraction of CSCs exposed to extreme hypoxia followed by reoxygenation. Here, we report that post-hypoxia/reoxygenation SPm+/ABCG2+ CSCs exerts defense against pathogen invasion that involves bystander apoptosis of non-infected CSCs. In an in vitro assay of cancer cell infection by Bacillus Calmette Guerin (BCG) or mutant Mycobacterium tuberculosis (Mtb) strain 18b (Mtb-m18b), the pathogens preferentially replicated intracellular to SPm+/ABCG2+ CSCs of seven cell lines of diverse cancer types including SCC-25 oral squamous cancer cell line. The conditioned media (CM) of infected CSCs exhibited direct anti-microbial activity against Mtb and BCG, suggesting niche defense against pathogen. Importantly, the CM of infected CSCs exhibited marked in vitro bystander apoptosis toward non-infected CSCs. Moreover, the CM-treated xenograft bearing mice showed 10- to 15-fold reduction (p < 0.001; n = 7) in the number of CSCs residing in the hypoxic niches. Our in vitro studies indicated that BCG-infected SPm+/ABCG2+ equivalent EPCAM+/ABCG2+ CSCs of SCC-25 cells underwent pyroptosis and released a high mobility group box protein 1 (HMGB1)/p53 death signal into the tumor microenvironment (TME). The death signal can induce a Toll-like receptor 2/4–mediated bystander apoptosis in non-infected CSCs by activating p53/MDM2 oscillation and subsequent activation of capase-3–dependent intrinsic apoptosis. Notably, SPm+/ABCG2+ but not SP cells undergoing bystander apoptosis amplified the death signal by further release of HMGB1/p53 complex into the TME. These results suggest that post-hypoxia SPm+/ABCG2+ CSCs serve a functional role as a tumor stemness defense (TSD) phenotype to protect TME against bacterial invasion. Importantly, the CM of TSD phenotype undergoing bystander apoptosis may have therapeutic uses against CSCs residing in the hypoxic niche.